2016
DOI: 10.1128/jvi.02717-15
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Cellular Cytotoxicity against Reactivated HIV-1-Infected Cells

Abstract: Lifelong antiretroviral therapy (ART

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…In addition, decreased amounts of Env at the cell surface due to efficient internalization also help the virus to avoid ADCC responses (17). In agreement with the need for HIV-1 to avoid exposing Env in the CD4-bound conformation, it was recently shown that forcing Env to adopt this conformation with small CD4-mimetic compounds (CD4mcs) sensitizes HIV-1-infected cells to ADCC responses (18)(19)(20). Accordingly, we recently reported that the transition of Env to the CD4-bound conformation is required for efficient interactions with ADCC-mediating antibodies (14).…”
mentioning
confidence: 90%
“…In addition, decreased amounts of Env at the cell surface due to efficient internalization also help the virus to avoid ADCC responses (17). In agreement with the need for HIV-1 to avoid exposing Env in the CD4-bound conformation, it was recently shown that forcing Env to adopt this conformation with small CD4-mimetic compounds (CD4mcs) sensitizes HIV-1-infected cells to ADCC responses (18)(19)(20). Accordingly, we recently reported that the transition of Env to the CD4-bound conformation is required for efficient interactions with ADCC-mediating antibodies (14).…”
mentioning
confidence: 90%
“…The kick-and-kill paradigm gained traction when it was demonstrated that latency reversal (kick) alone, with the LRA vorinostat, was insufficient to cause the death of infected cells in a postactivation in vitro latency model, whereas the addition of expanded HIV-specific CD8 + T cells resulted in infected cell elimination (5). Others have since reported similar results using additional in vitro latency models, combined with natural or engineered CD8 + T cells, or NK cells as effectors (9)(10)(11)(12)(13)(14). These results have motivated the translation of the kick-and-kill approach into clinical trials that, thus far, have failed to achieve reductions in infectious viral reservoirs (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently a small compound has been reported that inhibits Vpu mediated degradation of tetherin, providing a novel approach to sensitising infected cells for ADCC [140]. Together such approaches may play a role in cure strategies involving reactivation of latently infected cells by enhancing Env surface expression and revealing CD4i epitopes in Env, thereby sensitising them to elimination by ADCC [21].…”
Section: Hiv Evasion and Subversion Of Fcγr-mediated Ab Functionsmentioning
confidence: 99%
“…The assay measures LDH released upon cell lysis and has been used, for example, in recent studies examining the potential of HIV-1 specific ADCC in killing latently infected cells upon viral reactivation [21] [157].…”
Section: Cell Based Functional Assays For Fcr Activating Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation